Consumer-Based Strategy in Improving Business Post Covid-19 - Siera Syailendra; Ahmad Sopyan (Indonesian Journal of Innovation Multidisipliner Research, 2023)
The business world in various sectors has experienced a decline both during and after the COVID-19 pandemic. Various difficulties were faced by the business world in terms of distribution, supply of raw materials, the production process of goods and services, financial and capital difficulties, sales targets that were not achieved, obstruction of business networks and inadequate mastery of technology and information. The purpose of this research is to focus on business improvement strategies both during and post-pandemic that can be implemented for entrepreneurs in Indonesia. Descriptive analysis is used with a data collection approach through literature review (library study) sourced from previous studies. The results of the study show that in several fields of business, such as marketing, human resources, finance, health, and others, they can implement sustainable business strategies by increasing the production of goods and services along with providing excellent service to consumers in an effective and efficient manner so that businesses can continue and thrive. grow. The conclusion of this study is that business actors are required to have good knowledge management and absorptive capacity to improve their business performance. Furthermore, for further research to be able to examine more sharply with wider research sources in the scope of various business fields, with a more in-depth discussion with more comprehensive analytical methods both qualitatively and quantitatively.